Exposure to Plasma From Non-alcoholic Fatty Liver Disease Patients Affects Hepatocyte Viability, Generates Mitochondrial Dysfunction, and Modulates Pathways Involved in Fat Accumulation and Inflammation - Grossini, Elena; Garhwal, Divya Praveen; Calamita, Giuseppe; Romito, Raffaele; Rigamonti, Cristina; Minisini, Rosalba; Smirne, Carlo; Surico, Daniela; Bellan, Mattia; Pirisi, Mario (Frontiers in Medicine, 2021)
Changes of lipidic storage, oxidative stress and mitochondrial dysfunction may be involved in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Although the knowledge of intracellular pathways has vastly expanded in recent years, the role and mechanisms of circulating triggering factor(s) are debated. Thus, we tested the hypothesis that factors circulating in the blood of NAFLD patients may influence processes underlying the disease. Huh7.5 cells/primary human hepatocytes were exposed to plasma from 12 NAFLD patients and 12 healthy subjects and specific assays were performed to examine viability, H2O2 and mitochondrial reactive oxygen species (ROS) release, mitochondrial membrane potential and triglycerides content. The involvement of NLRP3 inflammasome and of signaling related to peroxisome-proliferator-activating-ligand-receptor-γ (PPARγ), sterol-regulatory-element-binding-protein-1c (SREBP-1c), nuclear-factor-kappa-light-chain-enhancer of activated B cells (NF-kB), and NADPH oxidase 2 (NOX2) was evaluated by repeating the experiments in the presence of NLRP3 inflammasome blocker, MCC950, and through Western blot. The results obtained shown that plasma of NAFLD patients was able to reduce cell viability and mitochondrial membrane potential by about 48 and 24% (p < 0.05), and to increase H2O2, mitochondrial ROS, and triglycerides content by about 42, 19, and 16% (p < 0.05), respectively. An increased expression of SREBP-1c, PPARγ, NF-kB and NOX2 of about 51, 121, 63, and 46%, respectively, was observed (p < 0.05), as well. Those effects were reduced by the use of MCC950. Thus, in hepatocytes, exposure to plasma from NAFLD patients induces a NAFLD-like phenotype by interference with NLRP3-inflammasome pathways and the activation of intracellular signaling related to SREBP-1c, PPARγ, NF-kB and NOX2.